Antibiotic Conjugated Fluorescent Carbon Dots as a Theranostic Agent for Controlled Drug Release, Bioimaging, and Enhanced Antimicrobial Activity. (18th March 2014) - Thakur, Mukeshchand; Pandey, Sunil; Mewada, Ashmi; Patil, Vaibhav; Khade, Monika; Goshi, Ekta; Sharon, Madhuri
Abstract : A novel report on microwave assisted synthesis of bright carbon dots (C-dots) using gum arabic (GA) and its use as molecular vehicle to ferry ciprofloxacin hydrochloride, a broad spectrum antibiotic, is reported in the present work. Density gradient centrifugation (DGC) was used to separate different types of C-dots. After careful analysis of the fractions obtained after centrifugation, ciprofloxacin was attached to synthesize ciprofloxacin conjugated with C-dots (Cipro @ C-dots conjugate). Release of ciprofloxacin was found to be extremely regulated under physiological conditions. Cipro @ C-dots were found to be biocompatible on Vero cells as compared to free ciprofloxacin (1.2 mM) even at very high concentrations. Bare C-dots ( ∼ 13 mg mL −1 ) were used for microbial imaging of the simplest eukaryotic model— Saccharomyces cerevisiae (yeast). Bright green fluorescent was obtained when live imaging was performed to view yeast cells under fluorescent microscope suggesting C-dots incorporation inside the cells. Cipro @ C-dots conjugate also showed enhanced antimicrobial activity against both model gram positive and gram negative microorganisms. Thus, the Cipro @ C-dots conjugate paves not only a way for bioimaging but also an efficient new nanocarrier for controlled drug release with high antimicrobial activity, thereby serving potential tool for theranostics.